Determination of Fe(II), Fe(III) and Fetotal in thermal water by ion chromatography spectrophotometry (IC-Vis). Issue 11 (1st September 2016) - Kaasalainen, Hanna; Stefánsson, Andri; Druschel, Gregory K.
ABSTRACT: Determination of iron speciation in water is one of the major challenges in environmental analytical chemistry. Here, we present and discuss a method for sampling and analysis of dissolved Fe(II), Fe(III), and Fetotal concentrations in natural thermal water covering a wide range of temperature, pH, chemical composition, and redox conditions. Various methods were tried in the collection, preservation, and storage of natural thermal water samples for the Fe(II) and Fe(III) determinations, yet the resultant Fe speciation determined was often found to be significantly affected by the methodology applied. Due to difficulties in preserving accurate Fe speciation in natural samples for later laboratory analysis, a field-deployed on-site method using ion-chromatography and spectrophotometry was developed and tested. The IC-Vis method takes advantage of ion chromatographic separation of Fe(II) and Fe(III), followed by post-column colour reaction and spectrophotometric detection, thus allowing analysis of Fe(II) and Fe(III) in a single 15-minute run. Additionally, Fetotal can be determined after sample oxidation. The analytical detection limits are 2 µg L −1 (LOD) using 200–1000 µL injection volumes and depend on the blank and reagent quality. The power of this method relies on the capability to directly determine a wide range of absolute and relative concentrations of Fe(II) and Fe(III) in the field. The field-deployed IC-Vis method was applied for the determination of Fe(II) and Fe(III) concentrations in natural thermal water with discharge temperatures ranging from 12°C to 95°C, pH between 2.46 and 9.75, and Fetotal concentrations ranging from a few μg L −c up to 8.3 mg L −1 .